2018
DOI: 10.1007/s12672-018-0336-7
|View full text |Cite
|
Sign up to set email alerts
|

Androgen Receptor and Ki67 Expression and Survival Outcomes in Non-small Cell Lung Cancer

Abstract: Lung cancer is the most common cause of cancer-related deaths worldwide with non-small cell lung cancer (NSCLC) making up most of these cases. Males have poorer overall survival compared to women following a lung cancer diagnosis. Many studies have focused on the effects of estrogen to explain higher survival rates among women, but few have looked at the effects of androgens. We describe the expression of the androgen receptor (AR) and Ki67 in lung cancer specimens in the Manitoba Tumor Bank (MTB) and correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 24 publications
(32 reference statements)
0
24
0
1
Order By: Relevance
“…Ki67 is expressed only in the nucleus of proliferating cells and reflects the proliferative activity of tumor cells. 9 Ki67 has been reported to be significantly upregulated in a variety of tumor tissues and cells, such as lung, 10 gastric, 11 colon, 12 ovarian, 13 and OS. 14 Our results are consistent with these reports.…”
Section: Dovepressmentioning
confidence: 99%
“…Ki67 is expressed only in the nucleus of proliferating cells and reflects the proliferative activity of tumor cells. 9 Ki67 has been reported to be significantly upregulated in a variety of tumor tissues and cells, such as lung, 10 gastric, 11 colon, 12 ovarian, 13 and OS. 14 Our results are consistent with these reports.…”
Section: Dovepressmentioning
confidence: 99%
“…And such application has not been found at clinical trial for lung cancer. Nevertheless, sex hormones and their receptors including AR showed influence on lung cancer in a mouse model, and AR expression together with Ki67 expression are associated with the survival outcome of non‐small‐cell lung cancer . As for liver cancer, AR is overexpressed in about 37% of hepatocellular carcinoma tumors, and AR overexpression stimulates oncogenic growth .…”
Section: Ar and Other Cancersmentioning
confidence: 99%
“…Nevertheless, sex hormones and their receptors including AR showed influence on lung cancer in a mouse model, 148 and AR expression together with Ki67 expression are associated with the survival outcome of non-small-cell lung cancer. 149 As for liver cancer, AR is overexpressed in about 37% of hepatocellular carcinoma tumors, and AR overexpression stimulates oncogenic growth. 150 In addition, it is reported that androgen promotes the growth of hepatocellular cancer cells by upregulating the transcription factor activity of ETS-1.…”
Section: Ar and Bladder Cancer Kidney Cancer Lung Cancer And LIVmentioning
confidence: 99%
“…Berardi et al [35] demonstrated a better OS in female non-small cell carcinoma patients with AR expression in carcinoma cells compared to those with tumors showing no AR expression. In contrast, Grant et al [36] demonstrated that AR expression has no association with recurrence or survival in modification with the Ki-67 labeling index. In the present study, only one case expressed AR receptor positivity and therefore cannot be interpreted because of the small number.…”
Section: The Present Study Investigated the Association Of Female Sexmentioning
confidence: 92%